Los hábitos alimentarios en el adulto mayor y su relación con los procesos protectores y deteriorantes en salud (2006)
ABSTRACT: Aim: To investigate the protective and deleterious aspects relative to nutrition and nourishment of elderly. Methodology: Research was focused on critical epidemiology and strategic monitoring. Quantitative and qualitative techniques were employed for the recollection of information. In the quantitative component a multiphase and stratified survey was selected while a directed survey was used for quantitative component. Results: Several unhealthy nutritional habits in this population from Caldas were identified, including a low intake of dairy products, meats, fruits and a high intake of fats. In some of the surveyed persons consumption was affected by a scarcity of food, while in other their mental status was more important. The participants identified low food consumption as a cause of hunger and sickness. They think that previously they had more food because they had the possibility to cultivate their plots while in their elderly years they experience familiar isolation making more difficult the acquisition of food..